TATA KELOLA ADMINISTRASI PROGRAM PENDIDIKAN KESETARAAN (PAKET A, B, C) DAN MUTU PEMBELAJARAN - Perawati Silalahi; Akhmad Suyatno; Lidia Aprileny Hutahaean (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Non-formal and equivalence education (Paket A, B, C) often faces challenges in learning quality due to weak administrative governance, manual systems, and limited digital literacy among tutors. This study aims to synthesize the concepts and practices of good administrative governance and their contribution to improving community learning quality in equivalence education programs. A qualitative literature review was conducted using thematic analysis. Relevant journals and documents published between 2015 and the present were systematically selected and analyzed, focusing on educational administration, digitalization, managerial supervision, and community empowerment. The findings reveal four key themes: comprehensive administration system structuring, digitalization and technological literacy, managerial supervision supported by Standard Operating Procedures (SOPs), and active community collaboration. Adapting these principles is crucial for equivalence programs to enhance operational efficiency, institutional accountability, and ultimately, the quality of learning services. Implementing structured, digital, and participatory administrative governance serves as a strategic foundation for overcoming resource limitations and ensuring sustainable educational quality for diverse learners.